Testing in the professions credentialing policies and practice - Davis-Becker, Susan; Buckendahl, Chad W. (NCME applications of educational measurement and assessment book series., 2017)
"Testing in the Professions focuses on current practices in credentialing testing as a guide for practitioners. With a broad focus on the key components, issues, and concerns surrounding the test development and validation process, this book brings together a wide range of research and theory -- from design and analysis of tests to security, scoring, and reporting. Written by leading experts in the field of measurement and assessment, each chapter includes authentic examples as to how various practices are implemented or current issues observed in credentialing programs. The volume begins with an exploration of the various types of credentialing programs as well as key differences in the interpretation and evaluation of test scores. The next set of chapters discusses key test development steps, including test design, content development, analysis, and evaluation. The final set of chapters addresses specific topics that span the testing process, including communication with stakeholders, security, program evaluation, and legal principles. As a response to the growing number of professions and professional designations that are tied to testing requirements, Testing in the Professions is a comprehensive source for up-to-date measurement and credentialing practices."--Amazon.com.